Pricing, price revision, and clinical value of anticancer drugs in Japan: a retrospective observational study - He, Jiaqi; Wei, Haibo; Yang, Yue (Frontiers in Pharmacology, 2025)
IntroductionThe high cost of anticancer drugs has raised concerns due to the financial burden on patients and pressure on healthcare systems. We examine the relation between pricing premiums, price revision, and clinical value for anticancer drugs approved in Japan.MethodsWe included anticancer drugs approved in Japan from 2013 to 2023. Differences in clinical value, as measured by the European Society for Medical Oncology Magnitude of Clinical Benefit Scale (ESMO-MCBS), among drugs receiving different premium proportions, were analyzed using the Mann-Whitney U test. Pearson correlation coefficients were calculated between treatment costs and clinical outcomes and value, including progression-free survival (PFS) gain, overall survival (OS) gain, objective response rate (ORR) gain and ESMO-MCBS. We also compared the magnitude of price revisions and price reductions with different clinical values. We used regression analysis to explore the association between clinical value, price revision, and influencing factors.ResultsOur cohort included 94 anticancer drugs and 119 key clinical trials. 39 drugs (41.49%) received premium pricing, while 55 drugs (58.51%) did not. Drugs with pricing premiums had higher ESMO scores than those without (3 vs. 2; P = 0.0013), with ESMO scores showing an increasing trend as the proportion of additional scores rose. Pearson correlation analysis revealed no significant association between daily treatment cost and ESMO score (r = 0.025, P = 0.79), PFS gain (r = −0.12, P = 0.37), OS gain (r = −0.25, P = 0.066), or ORR gain (r = 0.049, P = 0.8). Additionally, no significant differences were observed between high clinical value drugs (ESMO = 4–5) and low-to-medium clinical value drugs (ESMO = 1–3) in median price revision percentage and median price reduction percentage (−0.02% vs. 0.00%, P = 0.65; −9.86% vs. −13.55%, P = 0.607). Moreover, multivariate linear regression analysis revealed no association between ESMO scores, premium proportion, PFS gain, OS gain, ORR gain, approval year (P = 0.32; P = 0.06; P = 0.71; P = 0.06; P = 0.50; P = 0.51).DiscussionOur study found that Japan’s price premium reflects clinical value and provides incentives for high-clinical-value anticancer drugs. However, during both initial pricing and subsequent revision phases, there is room for improvement in aligning drug prices with clinical value. Policymakers should further refine pricing and revision systems to more effectively promote clinical value-driven drug pricing.